Restrukturisasi Kredit Macet Di PT Bank Rakyat Indonesia (Persero) Tbk Di Kecamatan Pringgarata Kabupaten Lombok Tengah Pasca Pandemi Covid 19 - Cahyani Safitri, Anggia; Subadi, Eka Jaya (Faculty of Law, University of Mataram, 2024)
This research aims to determine the factors causing bad credit at PT Bank Rakyat Indonesia (Persero) Tbk in Pringgarata after the Covid-19 pandemic and to determine the implementation of restructuring at PT Bank Rakyat Indonesia (Persero) Tbk in Pringgarata after the COVID-19 pandemic. This type of research is normative empirical with statutory, conceptual, and sociological approaches. The results of this research are the factors that cause bad credit at the Pringgarata branch of Bank Rakyat Indonesia, namely economic factors, unstable economic factors, and the impact of the ongoing Covid-19 pandemic. The overall financial situation has not yet recovered, making it difficult for debtors to fulfill their credit payment obligations. Bank Rakyat Indonesia Pinggarata branch implemented two types of restructuring, extending the term and paying the interest only. Bank Rakyat Indonesia causes debtors not to understand the restructuring program.